Exploring Gender Bias in the Elementary Level English Textbooks Published by the Punjab Board: A Case Study - Gul, Muhammad Asif; Ahmad, Riaz (Social Science Review Archives, 2025)
A mixed-method research design has been employed to investigate the frequency of different kinds of feminine erasure in the textbooks published by the Punjab Textbook Board in 2022. Working with English books for three elementary grades of Class 6, 7 and 8, data was analysed with two techniques. The first of them was textual analysis, and in the second, we used the literature method used in (Long, 2022). The findings have revealed that there are instances of every kind of feminine erasure patterns, though they show variance in different textbooks. Moreover, the results also showed close convergence with the results of the studies reported in the previous literature.